Aperts Syndrome with Intractable Acne Vulgaris - Fauzia Musbah (AlQalam Journal of Medical and Applied Sciences, 2020)
A pert syndrome as rare congenital disorders characterized by craniofacial and limb abnormalities. A 14 years old boy presented with a severe acne vulgaris for 4 years. In this case report, we discuss this rare condition and its treatment option.